Graphic Nonviolence: Framing “Good Trouble” in John Lewis’ March - Johannes C. P. Schmid (European Journal of American Studies)
This paper investigates the graphic memoir trilogy March that U.S. Congressman and civil rights leader John Lewis co-authored with Andrew Aydin and artist Nate Powell. The aim of the article is to describe how justice and injustice are framed in Lewis’ remembrance with regard to Lewis’ slogan of “good trouble.” In particular, it formulates an approach to investigate framing strategies that the work employs within the mediality of comics. Thus, the visual and material frames of the text are examined as techniques to facilitate political framing. Finally, the framing strategies of March will be correlated to the mobilization strategies of the civil rights movement.